The importance of the malleable implant salvage technique (MIST) in modern prosthetic urology - Tatem, Alex; Kovac, Jason R. (Translational Andrology and Urology, 2017)
Management of an infected penile prosthesis presents a challenging problem that is thankfully, a rare occurrence. For many years the standard of care was complete removal of the device followed by convalescence and a prolonged course of antibiotics. Unfortunately, the resulting corporal fibrosis made subsequent device placement much more challenging. This often necessitated insertion of a smaller implant with a higher risk of repeat infection and subsequent perforation.